Groz 200 - Balabanov, Alekseĭ, 1959-2013; Kuznet͡sova, Agnii͡a, 1985-; Poluyan, Alexey, 1965-2010; Stepanov, I͡Uriĭ, 1967-2010 (Kinokompaniya "CTB", 2007)
In 1984, in provincial Russia, the daughter of a communist party regional secretary is kidnapped and abused by a police officer. Meanwhile there is a brutal murder nearby, and military corpses return from Afghanistan. Based on actual events, an unflinching portrait of the decline of the Soviet era.